Isolasi Mikrobia Tanah di Sekitar Kandang Ayam Petelur dan Potensinya Sebagai Pereduksi Amonia dan Pengoksidasi Nitrit - PERMADI, Adhitya ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research aims was to isolate amonia reducing bacteria and nitrite oxidizing bacteria obtained from soil around the cage of layer industry and observe the isolates potential in reduction of amonia and oxidiation of nitrites. Data observed were growth of bacteria, bacteria colony diameter with or without NH4Cl, amonia and nitrite contrentation. We obtained 7 isolates of amonia reducing bacteria and 5 isolates nitrite oxidizing bacteria. Isolates that have the optimal ability to reduce amonia compounds, based on growth (optical density), the diameter of the colonies, and the concentration of ammonia were LS2 derived from soil around the cage of breeding of Setia layer Farm Kaliurang. The average data of colony diameter of LS2 isolate were 0.35 Â± 0.12 mm (NH4Cl) and 0.16 Â± 0,09 mm (without NH4Cl) The average decrease of ammonia concentration of LS2 were 3.7 ppm, respectively in 24 hours. The best isolates which have ability to increased nitrate concentration was SF isolate and the increasing average was 0.9 ppm.